Food waste valorization: guidance for integrating sustainable management strategies - Hafyan, Rendra Hakim; Kumar, Vinod; Maity, Sunil K.; Sadhukhan, Jhuma; Gadkari, Siddharth (MDPI, 2026)
Food waste (FW) is a major global challenge with significant economic and environmental costs, yet its nutrient-rich composition also offers an opportunity for valorization into high-value biochemicals and biofuels within a circular bioeconomy. Effective FW management requires systematic frameworks that balance environmental performance, economic returns, and social acceptance, a challenge that is particularly difficult in developing countries where technical, financial, and participation barriers persist. This review proposes a strategic, step-by-step approach to enhance current FW management through the objective integration of biorefinery pathways producing biochemicals and biofuels products. Both biochemical and thermochemical conversion routes are evaluated against industrial yield benchmarks, market value, and end-use specifications to identify the products and processes most capable of enhancing sustainability. The review further presents a framework for multi-objective optimization (MOO) that simultaneously addresses economic, environmental, and social objectives, and for incorporating decision-maker preferences into the selection of optimum solutions. By coupling sustainability assessment with structured decision support, this review provides practical guidance for selecting FW management strategies that are economically viable, environmentally sound, and socially acceptable.
This article belongs to the Special Issue Advances and Applications of Food Industry By-Products
Keywords: 38 Economics; 4104 Environmental Management; 41 Environmental Sciences; 12 Responsible Consumption and Production; food waste; food waste management; sustainability assessment; circular bioeconomy; decision making